Systemic Approach in Latino Families Surviving Domestic Violence in the United States - Garcia-Leeds, Claudia Beatriz (2017)
The goal of this study was to attempt to create a more effective treatment model by leveraging the knowledge and skill sets of those who work most closely with these families in crisis. The participants, who consisted of the direct care staff of the Latino Domestic Violence Program (LDVP) in Philadelphia, were interviewed individually, and the data was analyzed in accordance with grounded theory methodology. The participants' responses served to bring to the fore a number of important issues. The participants helped identify two main elements that needed to be part of an ideal program. 1: The program must be equipped to address all the biopsychosocial needs experienced by the family (financial, occupational, educational and mental health needs). Undocumented and non-English speaking clients’ needs must be also considered when developing a program for Latino families. 2: We should avoid utilizing a model based on mainstream (United States) culture that does not respond to the needs of the community. It is important that the staff be trained in various theories/models that would help in the understanding of the clients’ culture.